Canine IVM With SOF Medium, Insulin-Transferrin-Selenium, and Low O2 Tension Improves Oocyte Meiotic Competence and Decreases Reactive Oxygen Species Levels - Duque Rodriguez, Matteo; Cittadini, Camila O.; Teplitz, Gabriela M.; De Stefano, Adrian; Lombardo, Daniel M.; Salamone, Daniel F. (Frontiers in Cell and Developmental Biology, 2021)
Assisted reproductive technologies in canine species are limited due to the low efficiency of in vitro maturation (IVM). Unlike other mammals, bitches ovulate oocytes in the germinal vesicle stage and complete metaphase II (MII) after 48–72 h in the oviductal environment and become fertilizable. For this reason, we compared two different IVM media, synthetic oviductal fluid (SOF) supplemented with 8% bovine serum albumin (BSA) or a mixture of 8% BSA–2.5% fetal bovine serum (FBS) and TCM-199 with 10% FBS. Additionally, we evaluated the effect of supplementation with insulin-transferrin-selenium (ITS) and low O2 tension in oocyte maturation, reactive oxygen species (ROS) levels, membrane integrity, and embryo development following parthenogenetic activation (PA). After 72 h of culture, SOF + BSA, SOF + BSA + FBS, and TCM-199 + FBS show 5, 7, and 4% of MII, respectively, without a statistical difference. However, SOF + BSA produced significantly higher degeneration rates compared to SOF + BSA + FBS (44 and 23%, respectively). Remarkably, supplementation with 1 μl/ml of ITS under high O2 tension demonstrated a beneficial effect by improving maturation rates up to 20% compared to the other groups. Low O2 tension increased maturation rates to 36.5%, although there were no statistical differences compared to high O2 tension in the presence of ITS. Lower ROS levels and higher integrity of the cytoplasmic membrane were found in the presence of ITS despite no differences in maturation rates under low O2 tension groups. Additionally, after PA, 1% development until the eight-cell stage was obtained after activation of in vitro-matured oocytes in the presence of ITS. Taken together, these results indicate that SOF supplemented with 8% BSA and 2.5% FBS is suitable for IVM of canine oocytes and ITS supplementation was beneficial for both high and low O2 tension. Furthermore, the addition of ITS in the cultured system lowers ROS levels and increases membrane integrity in domestic dog oocytes after IVM.